Impact of substance abuse among adolescents: a narrative review - Hemamalini, M.; Elamathi, E.; Rajathi, S.; Narayanasamy, K. (International Journal Of Community Medicine And Public Health, 2025)
Substance abuse among adolescents are considered as a critical public health issue which leads to impact on individual development and societal well-being. Around 1.5 crore (15 million) minors aged between 10–17 years uses substance in India and 34% used any substances in Tamil Nadu. There are no enough evidences on impact of substance abuse. Hence, this study aimed to explore the various impact of substance abuse among adolescents. The literature search was carried out in Pub-med central, Google scholar and Web of science databases with suitable search terminology like impact of substance abuse, addictions, drug abuse, drug dependence, substance use disorders drug user, drug intoxication, and toxicity. In addition, demographic variables, new innovative policies and programs for substance abuse among adolescents in India were reported in the present review. Understanding the impact of substances among adolescents helpful in development of targeted health policies and community-based programs. It ultimately promotes the healthier lifestyles and also enhances future outcomes among adolescents.